Navigating nasal swelling: the diagnostic journey to osteoblastic osteosarcoma - Lee, Tiong Siew; Binti Roslim, Siti Nor’ain; Hitam, Shahrul Bin; Omar, Noorjehan Binti; Abu Bakar, Mohd Zulkiflee Bin (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Nasal swelling is frequently encountered in ENT, but diagnosing osteosarcoma in the head and neck region is quite uncommon. Diagnosing and managing craniofacial osteosarcoma is challenging due to its rarity and nonspecific radiological features, which often lead to biopsy errors. Additionally, the proximity to vital structures complicates achieving complete resections. MRI is the gold standard for detailed assessment of osteosarcoma, offering crucial insights into tumor extent, soft tissue involvement, and proximity to surrounding structures for effective treatment planning and response monitoring. CT supports this by aiding in biopsy planning, staging, and detecting metastases, particularly in the chest. Craniofacial osteosarcoma treatment lacks consensus but generally prioritizes surgery, with negative margins crucial for better outcomes. Adjuvant chemotherapy can boost survival, while radiotherapy is used when complete surgery is not possible. In this case, we bring your attention to a 31-year-old gentleman who presented with progressive and painless nasal swelling for 6 months prior to visiting the ORL clinic, where a final diagnosis of osteoblastic osteosarcoma was made after history, examination, imaging, and histopathology results.